The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/978-3-031-44067-0_29
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Search Result Stances to Opinionated People

Zhangyi Wu,
Tim Draws,
Federico Cau
et al.

Abstract: published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…Epstein and Robertson (2016) showed that the magnitude of SEME could be reduced to some extent by such alerts (cf. Tapinsky et al, 2018;Wu et al, 2023). Alerts of this sort could also be used to flag the rising tide of online "misinformation" -an imperfect but not entirely unreasonable method for appeasing free speech advocates without suppressing content (Nekmat, 2020;Shin et al, 2023;cf.…”
Section: Implications and Concernsmentioning
confidence: 99%
“…Epstein and Robertson (2016) showed that the magnitude of SEME could be reduced to some extent by such alerts (cf. Tapinsky et al, 2018;Wu et al, 2023). Alerts of this sort could also be used to flag the rising tide of online "misinformation" -an imperfect but not entirely unreasonable method for appeasing free speech advocates without suppressing content (Nekmat, 2020;Shin et al, 2023;cf.…”
Section: Implications and Concernsmentioning
confidence: 99%